IMPLEMENTASI METODE IBTIDAI UNTUK MENINGKATKAN MAHARAH QIRA’AH PADA KELAS WUSTHO 2 MADRASAH DINIYAH AL MANSHUR POPONGAN KLATEN - Muhammad Ilham Burhanudin; Dzaky Nabil Al-Hakim; Pitri Nurmandani; Habib Muhammad Abdush Shomad; Fauzi Annur (Universitas Islam Negeri Palopo, 2026)
Inappropriate Arabic teaching methods often hinder students’ ability to comprehend kitab kuning (classical Islamic texts). In the Wustho 2 Class at Madrasah Diniyah Al-Manshur Popongan Klaten, students face difficulties in independently understanding religious texts despite possessing basic grammatical knowledge. This study aims to analyze the implementation of the Ibtidai method, along with its supporting and inhibiting factors, in enhancing maharah qira’ah fiqh (reading skills in jurisprudence). The novelty of this research lies in its integrative analysis using E. Mulyasa’s educational taxonomy and Mulyadi’s implementation framework. This study employed a qualitative approach with a case study design. Data were gathered through semi-structured interviews and further validated via non-participant observation and documentary analysis, then analyzed using the Miles and Huberman interactive model. The results indicate that the Ibtidai method effectively facilitates students’ literacy transition by shifting the focus of difficulty from technical-mechanical aspects toward analytical-conceptual skills. The primary constraints identified are the heavy dominance of rote learning and low self-regulated learning among students. Ketidaktepatan metode pembelajaran bahasa Arab sering kali menghambat kemampuan literasi kitab kuning santri. Di Kelas Wustho 2 Madrasah Diniyah Al-Manshur Popongan Klaten, santri mengalami kesulitan memahami teks keagamaan secara mandiri meskipun telah memiliki dasar gramatikal. Penelitian ini bertujuan untuk menganalisis implementasi metode Ibtidai serta faktor pendukung dan penghambatnya dalam meningkatkan maharah qira’ah fiqh. Kontribusi kebaruan penelitian ini terletak pada pengkajian integratif menggunakan taksonomi pendidikan E. Mulyasa dan perspektif implementasi Mulyadi. Metode penelitian yang digunakan adalah kualitatif dengan desain studi kasus. Hasil penelitian menunjukkan bahwa metode Ibtidai efektif memfasilitasi masa transisi literasi santri dengan menggeser fokus kesulitan dari aspek teknis-mekanis menuju kemampuan analitis-konseptual. Kendala utama yang ditemukan adalah tingginya dominasi hafalan murni (rote learning) dan rendahnya kemandirian belajar santri (self-regulated learning).